Análisis y mejoramiento de procesos constructivos, en los proyectos de la empresa VIVICON - Salazar-Corrales, Kevin (Instituto Tecnológico de Costa Rica, 2017)
The objective of this document is to determine the productivity and performance of two building processes within the masonry work of two residential condominiums (Avenir and Cedro Real) built by Vivicon S.A. These two processes, which are the most interesting for the company, where first selected by expert professional criteria and later subjected to observations and samplings that resulted in data to determine productivity and performance indexes. This information was useful to apply techniques such as Crew Balance, Five Minute Rating, and Work Sampling, as well as to represent processes graphically using value stream maps, flow and Ishikawa charts. All of which was intended to analyze results and recommend improvements. Key aspects were found that affect the processes causing lower productivity, some with greater impact as for the site design and carriage which involve time and cost the company would not have not considered there had not been any productivity analysis. The concepts of productivity and performance cannot be used indistinctively as they work together, but are two different principles. The obtained data is located in a database created to facilitate the process of budgeting and programming.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Productividad; Base de datos; Rendimiento; Flujos; Diagramas